Exploring the interplay between elite athletes and sport equipment in the quest for performance: A case study in sailing - Terrien, E.; Huet, B.; Saury, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction From a phenomenological perspective, it is classically assumed that when sport equipment is used by expert athletes, it is so well incorporated to the athlete`s body that it becomes transparent, disappearing from the athlete`s awareness. However, few studies have investigated the perceptual experiences of expert athletes using their equipment to challenge this assumption. These studies focus on small equipment such as backpacks or ice axes, showing that even these types of equipment can have a significant presence in elite athlete`s experience. We pursued this exploration in the sport of windsurfing and more specifically in IQfoil (i.e. the Olympic windsurfing class). Indeed, in IQfoil, the size and characteristics of the equipment contrasts with those of the previous studies, creating a favorable situation of research to contribute to the understanding of the interplay between human and sport equipment.